Eksistensi Atraksi Hombo Batu (Lompat Batu) Sebagai Tradisi dalam Peningkatan Kunjungan Wisata di Desa Bawamataluo Kecamatan Fanayama Kabupaten Nias Selatan - Sebastinus Gulo; Sudirman Lase; Bambang T.J Hutagalung; Harisan Boni Firmando; Liyus Waruwu (Pusat Riset dan Inovasi Nasional, 2026)
The Hombo Batu attraction is a cultural tradition of the Nias people that is still preserved to this day, especially in Bawamataluo Village. This tradition not only serves as a cultural heritage and a symbol of maturity for Nias men, but has also developed into a cultural tourism attraction that has economic value for the local community. This study aims to analyze the existence of the Hombo Batu attraction as a cultural tradition and its role in increasing tourist visits to Bawamataluo Village. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants included traditional leaders, Hombo Batu attraction actors, village tourism managers, and tourists. The results of the study indicate that the existence of the Hombo Batu attraction is still maintained through the inheritance of cultural values from generation to generation and support from the local community. In addition, Hombo Batu has proven to be a major attraction that is able to increase interest in domestic and international tourists. However, the management of this attraction still faces several obstacles, such as limited promotion and tourism support facilities. This study concludes that the Hombo Batu attraction plays a strategic role in the development of cultural tourism in Bawamataluo Village and needs to be supported by sustainable management to maintain its cultural value and economic benefits.